An Industrial PID Data Repository for Control Loop Performance Monitoring (CPM). Issue 4 (2018) - Bauer, Margret; Auret, Lidia; Roux, Derik le; Aharonson, Vered
Abstract: Control loop performance monitoring methods to detect problems in PID loops are developed and tested using industrial data sets. The data is captured from the process, passed on to the researcher who tries out new detection and diagnosis methods. The data is not generally shared with other researchers working on similar problems. The authors therefore have implemented a data repository to categorise and store the data so that it becomes accessible to all researchers. Existing methods can be compared and enhanced using the data sets. This paper describes the context of CPM as well as the data repository. The repository is set up, hosted and maintained by the South African Council for Automation and Control using a professional web developer.